COMPETITIVE ADVANTAGE AS A MEDIATING VARIABLE BETWEEN E-COMMERCE AND PRODUCT INNOVATION TOWARDS MARKETING PERFORMANCE OF SMALL AND MEDIUM-SIZED ENTERPRISES IN KENDAL - Udriyah Udriyah; Yuni Pambreni; Zakia Maulida Antono (TECHNO-SOCIO EKONOMIKA, 2023)
Path analysis is used on this study in studying the effect of e-commerce and product innovation on competitive advantage and the impact on marketing performance of SMEs in Kendal Regency, Central Java. The method of collecting data is by using a questionnaire. The sample is amounted to 100 SMEs in Kendal, Central Java, Indonesia. The result indicates that e-commerce together with product innovation have positively significant influence partially and simultaneously toward competitive advantage of SMEs in Kendal. The competitive advantage has a significant positive influence on the marketing performance of SMEs in Kendal. E-commerce together with product innovation mediating by competitive advantage positively significant effecting on marketing performance of SMEs in Kendal, directly and indirectly. The outcomes of this research answered the effect of e-commerce and product innovation toward competitive advantage and marketing performance of SMEs in Kendal, Central Java. The SMEs owner can optimize and improve the marketing performance by escalating use of e-commerce and optimizing product innovation that will affect the increasing competitive advantage and marketing performance.